C/N Vacancy Co‐Enhanced Visible‐Light‐Driven Hydrogen Evolution of g‐C3N4 Nanosheets Through Controlled He+ Ion Irradiation (Solar RRL 4∕2019). Issue 4 (8th April 2019) - Wang, Xuening; Wu, Liang; Wang, Zhaowu; Wu, Hengyi; Zhou, Xuemei; Ma, Hongyu; Zhong, Huizhou; Xing, Zhuo; Cai, Guangxu; Jiang, Changzhong; Ren, Feng
Abstract : Defect engineering is an important method for enhancing photocatalytic performance. In article no.1800298, Zhaowu Wang, Feng Ren, and co‐workers successfully design and prepare a defective g‐C3N4 photocatalyst via ion irradiation technology, achieving simultaneous introduction of C‐ and N‐ vacancies and the control of vacancy concentration, thus realizing a remarkable improvement in photocatalytic hydrogen production performance.